A revision of the Habrocerinae of the world. IV. A new species of Habrocerus from China and additional records (Coleoptera: Staphylinidae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2008)
Habrocerus splendens sp. n. (China: Yunnan) of the H. capillaricornis group is described and illustrated. Additional records of Habrocerinae are reported, among them first records of H. pisidicus Korge from France and Croatia, of H. cyprensis Assing & Wunderle from Turkey, and a female-based first record of H. ibericus Assing & Wunderle from Morocco.KeywordsColeoptera, Staphylinidae, Habrocerinae, Habrocerus, Nomimocerus, world, China, taxonomy, new species, new records.Nomenclatural Actssplendens Assing, 2008 (Habrocerus), spec. n.